Lower Intrinsic ADP-Stimulated Mitochondrial Respiration Underlies In Vivo Mitochondrial Dysfunction in Muscle of Male Type 2 Diabetic Patients - Phielix, Esther; Schrauwen-Hinderling, Vera B.; Mensink, Marco; Lenaers, Ellen; Meex, Ruth; Hoeks, Joris; Kooi, Marianne Eline; Moonen-Kornips, Esther; Sels, Jean-Pierre; Hesselink, Matthijs K.C.; Schrauwen, Patrick (Diabetes (New York, N.Y.), 2008)
Lower Intrinsic ADP-Stimulated Mitochondrial Respiration Underlies In Vivo Mitochondrial Dysfunction in Muscle of Male Type 2 Diabetic Patients Esther Phielix 1 , Vera B. Schrauwen-Hinderling 1 2 , Marco Mensink 1 , Ellen Lenaers 3 , Ruth Meex 3 , Joris Hoeks 1 , Marianne Eline Kooi 2 , Esther Moonen-Kornips 1 3 , Jean-Pierre Sels 4 , Matthijs K.C. Hesselink 3 and Patrick Schrauwen 1 1 Department of Human Biology, Maastricht University, Maastricht, the Netherlands 2 Department of Radiology, Maastricht University Hospital, Maastricht, the Netherlands 3 Department of Human Movement Sciences, Maastricht University, Maastricht, the Netherlands 4 Department of Internal Medicine, Maastricht University Hospital, Maastricht, the Netherlands Corresponding author: Dr. Patrick Schrauwen, p.schrauwenathb.unimaas.nl Abstract OBJECTIVE— A lower in vivo mitochondrial function has been reported in both type 2 diabetic patients and first-degree relatives of type 2 diabetic patients. The nature of this reduction is unknown. Here, we tested the hypothesis that a lower intrinsic mitochondrial respiratory capacity may underlie lower in vivo mitochondrial function observed in diabetic patients. RESEARCH DESIGN AND METHODS— Ten overweight diabetic patients, 12 first-degree relatives, and 16 control subjects, all men, matched for age and BMI, participated in this study. Insulin sensitivity was measured with a hyperinsulinemic-euglycemic clamp. Ex vivo intrinsic mitochondrial respiratory capacity was determined in permeabilized skinned muscle fibers using high-resolution respirometry and normalized for mitochondrial content. In vivo mitochondrial function was determined by measuring phosphocreatine recovery half-time after exercise using 31 P-magnetic resonance spectroscopy. RESULTS— Insulin-stimulated glucose disposal was lower in diabetic patients compared with control subjects (11.2 ± 2.8 vs. 28.9 ± 3.7 μmol · kg −1 fat-free mass · min −1 , respectively; P = 0.003), with intermediate values for first-degree relatives (22.1 ± 3.4 μmol · kg −1 fat-free mass · min −1 ). In vivo mitochondrial function was 25% lower in diabetic patients ( P = 0.034) and 23% lower in first-degree relatives, but the latter did not reach statistical significance ( P = 0.08). Interestingly, ADP-stimulated basal respiration was 35% lower in diabetic patients ( P = 0.031), and fluoro-carbonyl cyanide phenylhydrazone–driven maximal mitochondrial respiratory capacity was 31% lower in diabetic patients ( P = 0.05) compared with control subjects with intermediate values for first-degree relatives. CONCLUSIONS— A reduced basal ADP-stimulated and maximal mitochondrial respiratory capacity underlies the reduction in in vivo mitochondrial function, independent of mitochondrial content. A reduced capacity at both the level of the electron transport chain and phosphorylation system underlies this impaired mitochondrial capacity. Footnotes Published ahead of print at http://diabetes.diabetesjournals.org on 4 August 2008. Readers may use this article as long as the work is properly cited, the use is educational and not for profit, and the work is not altered. See http://creativecommons.org/licenses/by-nc-nd/3.0/ for details. The costs of publication of this article were defrayed in part by the payment of page charges. This article must therefore be hereby marked “advertisement” in accordance with 18 U.S.C. Section 1734 solely to indicate this fact. Accepted March 19, 2008. Received February 27, 2008. DIABETES